Study of CT-Guided Localization in Pulmonary Nodule Resection - Cheng Zhang; Ke Min; Hailong Zhao; Fengchang Zheng (Applied Bionics and Biomechanics)
Objective. In recent years, with the attention of the general people to health, the surgical treatment of small nodules has become necessary. However, some nodules are too small, too deep, or difficult to reach, and it is difficult to accurately locate small nodules in the process of routine resection. In order to solve this problem and increase the success rate of puncture surgery, this study analyzed the application value of zoning localization method guided by CT in patients with pulmonary nodules. Methods. The clinical history of patients with pulmonary nodules treated in Anhui Third Affiliated Hospital was retrospectively studied and analyzed. 97 patients with solitary pulmonary nodules treated in Anhui Third Affiliated Hospital from June 2021 to August 2021 were divided into observation group and reference group according to whether CT-guided localization method was used during operation. The operation rate, 1-year survival rate, recurrence rate, and pulmonary nodule metastasis rate of the two groups were compared; the results showed that the CT-guided zonal localization method was long and short, accurate, safe, and reliable. Comprehensive comparison through market survey on postoperative recovery compares the variability of patient data by using the statistical bivariatet-calibration method and using sensitivity specificity to analyze whether the CT-guided positioning method has advantages.Results. The data underlying the results presented in the study are available within the manuscript. The results showed that there were 37 cases of pulmonary nodules, accounting for 38.14%; there were 8 patients with lung cancer, accounting for 8.24%; the proportion of diagnosis and analysis results of pulmonary nodules in hospitalized patients was significant; the medical history and clinical diagnosis information of 37 patients with pulmonary nodules were tracked and analyzed in detail. The diagnostic results were as follows: 8 patients (21.62%) with stage I, 11 patients (29.72%) with stage II, and 18 patients (48.64%) with stage III. The proportion of severe patients in the third stage was significantly higher than that in the first two stages; the results of CT-guided localization and conventional surgical resection were T<10.000 and P<0.05; the observation of prognosis and quality of life in the later stage of resection treatment showed that the observation group had obvious advantages over the reference group in terms of postoperative survival rate, recurrence rate, and nodule deterioration rate. The results show that the CT-guided zoning positioning operation is accurate, safe, and reliable.Conclusion. The application of the CT-guided localization in the surgical treatment of pulmonary nodules is more safe and reliable. It can not only reduce the trauma but also improve the success rate of operation and reduce postoperative complications. It has the value of clinical promotion.